Evaluation of different potassium management options under prevailing dry and wet seasons in puddled, transplanted rice - Mohapatra, Suchismita; Rout, Kumbha Karna; Khanda, Chandramani; Mishra, Amit; Yadav, Sudhir; Padbhushan, Rajeev; Mishra, Ajay Kumar; Sharma, Sheetal (MDPI, 2023)
The present field experiment was conducted in both dry season (DS) and wet season (WS) from 2014–2015 to evaluate the influence of different potassium (K) management options (graded doses of inorganic K fertilizer alone and combined with foliar and straw incorporation) on the rice yield, nutrient uptake, and soil K balance under puddled, transplanted rice in acidic soil. The results showed that rice yields were higher under WS as compared to the DS crop. Among treatments, K40 + Kspray, i.e., the combination of inorganic K fertilizer (40 kg K2O ha−1) along with a foliar spray of K (1% KNO3) at the panicle initiation stage, produced the highest grain yield in both seasons; however, it was on par with treatments K80, i.e., the highest dose of inorganic K fertilizer (80 kg K2O ha−1) alone, and K30 + Kstraw i.e., integrated use of inorganic K fertilizer (30 kg K2O ha−1) and straw (3 t ha−1, 45 kg K2O ha−1). Application of 80 kg K2O ha−1 through inorganic fertilizer alone had the maximum K uptake at the harvest stage in both seasons. DS rice had a higher K/N and K/P ratio than the WS. The treatments applied with inorganic K fertilizers, either soil or foliar applications, had negative K balance in both seasons; however, treatments applied with organic sources of K, i.e., rice straw alone or integrated with inorganic K fertilizers, had positive K balances in the soil. Therefore, this study shows that the integrated use of inorganic K fertilizer and 3 t ha−1 rice straw (K30 + Kstraw) can be a recommended option for a better K management strategy for crop yields and soil sustainability in acid soils. However, in terms of greenhouse gas (GHG) estimation, incremental doses of soil-applied K fertilizer along with straw aggravate the GHGs emission in the rice–rice cropping system, and among all treatments, K40 + Kspray is the promising treatment which requires intensive investigation for drawing an overall conclusion.